Sentence Problem pada Penulisan Essay Mahasiswa Program Studi Sastra Inggris - Amirudin Amirudin; Tutik Ratna Ningtyas (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2023)
Essay writing is a skill that must be mastered by students, especially English Literature Study Program students. Writing essays in English is a challenge in itself which of course has a lot of problems in the process. In writing essays in English, of course, you have to follow the correct writing rules. Mastery of several important aspects of writing including grammar, vocabulary, content, mechanism and organization is very important to be able to create good and easy-to-understand writing. Besides that. there are several things that need to be considered to create accuracy in writing such as sentence structure, cohesive devices in writing, and so on. In this study, the focus is on the problem of writing sentences. This study investigates sentence writing problems such as sentence fragments, run-on sentences, parallel structures, comma connections, and so on which are often encountered. This study involved semester student essays 6 English Literature study programs. The reason for selecting sixth semester students for the English Literature study program is because at this level students have already taken Writing and Grammar courses. This study aims to explain the phenomena of the sentence problems. This research is expected to contribute to the academic field. The contribution in question is a contribution in improving learning strategies related to writing. Therefore the author chose the research title "Sentence Problem in essay writing for students of the English Literature study program, Pamulang University".